Program Evaluation
128 p.
Keywords: Please glance over the questions that follow and read the answers to those that are of interest. Q: What does this manual do? A: This manual guides the user through designing an evaluation. A: Who can use it? A: Anyone interested or involved in evaluating professional trammg or inservice education programs. The primary users will be staff members who are doing their own program evaluation-maybe for the first time. (Experienced evaluators or other professional educators can find useful guides and worksheets in it.) Q: If I work through this manual, what will I accomplish? A: You will develop one or more evaluation designs, and perhaps you'll also use the designs to evaluate something to make it better or to document its current value. Q: What is an evaluation design? A: An evaluation design is a conceptual and procedural map for getting important information about training efforts to people who can use it, as shown in the graphic below.